8+7(b+2)=-3+6(b+5)

Simple and best practice solution for 8+7(b+2)=-3+6(b+5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8+7(b+2)=-3+6(b+5) equation:


Simplifying
8 + 7(b + 2) = -3 + 6(b + 5)

Reorder the terms:
8 + 7(2 + b) = -3 + 6(b + 5)
8 + (2 * 7 + b * 7) = -3 + 6(b + 5)
8 + (14 + 7b) = -3 + 6(b + 5)

Combine like terms: 8 + 14 = 22
22 + 7b = -3 + 6(b + 5)

Reorder the terms:
22 + 7b = -3 + 6(5 + b)
22 + 7b = -3 + (5 * 6 + b * 6)
22 + 7b = -3 + (30 + 6b)

Combine like terms: -3 + 30 = 27
22 + 7b = 27 + 6b

Solving
22 + 7b = 27 + 6b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-6b' to each side of the equation.
22 + 7b + -6b = 27 + 6b + -6b

Combine like terms: 7b + -6b = 1b
22 + 1b = 27 + 6b + -6b

Combine like terms: 6b + -6b = 0
22 + 1b = 27 + 0
22 + 1b = 27

Add '-22' to each side of the equation.
22 + -22 + 1b = 27 + -22

Combine like terms: 22 + -22 = 0
0 + 1b = 27 + -22
1b = 27 + -22

Combine like terms: 27 + -22 = 5
1b = 5

Divide each side by '1'.
b = 5

Simplifying
b = 5

See similar equations:

| C^2(2*c)=20 | | 2(x+4)-5=2x-3 | | 2(4y+10)=5y+32 | | 3(m-7)=9 | | -5x+7=12 | | 36+15=17x | | 24a-8-10a=2(4-7a) | | 0.4x-36=0.5x | | 0.5x+6=3 | | x+2*y-1=2 | | 2x-8=6x-12 | | -14y-5=75 | | 5n+2(3n-6)=12 | | 8(w-8)=7(5+w) | | 3m=8m | | (9x+9)(3x+3)= | | 5c^2-31c=28 | | T-15=-11 | | (2x+5)=68 | | 2n+8n=20 | | 8s-32-5s=-5 | | -t+5=t-9 | | n^2+4n-3=0 | | x=2x-4.6 | | 14n-21=15n-20 | | h=-36t^2+qt+d | | 54x^2+72x= | | x^3-11x^2-202x+440=0 | | 6x-5=5x+3 | | 19b-4=73 | | x-8.4=-4.7 | | 70=10-3x |

Equations solver categories